Implementation of Religious Moderation Values ​​in Early Childhood through Islamic Religious Education - Syaikhon, Muhammad; Nanang Rokhman Saleh; Zumrotul Huliyah (CV. Creative Tugu Pena, 2024)
RA TAAM Adinda is an educational institution that prioritizes religious values in early childhood education, with one of its main focuses being the value of religious moderation. This research aims to analyze the process of implementing religious moderation values in early childhood at RA TAAM Adinda and to identify the supporting and inhibiting factors. This study employs a qualitative approach in the form of a case study, with research subjects including educators, students, and parents. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing or verification. The results of the study show that the implementation of religious moderation values in early childhood through Islamic education at RA TAAM Adinda is carried out through the processes of planning, execution, and evaluation. Planning is conducted by incorporating religious moderation values into the school curriculum, annual, semester, weekly programs, and daily learning programs. The execution of religious moderation values is integrated into learning activities, role modeling, and daily habits. The evaluation process follows the learning evaluation through observation results, student works, performance, conversations, and assignments. Supporting factors for implementing religious moderation values include the presence of these values in the curriculum, the school's motivation to achieve high-quality graduates, and adequate facilities and infrastructure. Meanwhile, the inhibiting factors include the diverse characteristics of children, the lack of student focus in receiving the material, and environmental influences.